Urgensi Pendidikan Multikultural di Sekolah dan Masyarakat Indonesia sebagai Bentuk Keragaman Budaya - Wirda, Aina; Dhoni, Amalia Rhoma; Ulva, Devi Aulia; Fatmawati, Fatmawati; Listiana, Listiana; Banani, Putri Fauziah (Lembaga Yasin AlSys, 2023)
The study is in the background by the pluralistic and pluralistic societies of diverse ethnic, cultural, language, culture, religion and class societies. Each community group has different characteristics and interests. In this study the author uses qualitative analyses that go through the phases of data collection, classify, connect with existing theories and problems, and then draw conclusions to determine the outcome. Learning multiculturalism may be a precaution for prejudice and conflict between groups, for through multicultural studies students learn to appreciate different ethnic cultures, assess their strengths and deficiencies, and eventually they will accept that there is no perfect culture and absolutely no benefit. Multicultural education could be a tool for Indonesia to preserve the unity of the nation.